5-t-3=-1+2(t-3)

Simple and best practice solution for 5-t-3=-1+2(t-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-t-3=-1+2(t-3) equation:


Simplifying
5 + -1t + -3 = -1 + 2(t + -3)

Reorder the terms:
5 + -3 + -1t = -1 + 2(t + -3)

Combine like terms: 5 + -3 = 2
2 + -1t = -1 + 2(t + -3)

Reorder the terms:
2 + -1t = -1 + 2(-3 + t)
2 + -1t = -1 + (-3 * 2 + t * 2)
2 + -1t = -1 + (-6 + 2t)

Combine like terms: -1 + -6 = -7
2 + -1t = -7 + 2t

Solving
2 + -1t = -7 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
2 + -1t + -2t = -7 + 2t + -2t

Combine like terms: -1t + -2t = -3t
2 + -3t = -7 + 2t + -2t

Combine like terms: 2t + -2t = 0
2 + -3t = -7 + 0
2 + -3t = -7

Add '-2' to each side of the equation.
2 + -2 + -3t = -7 + -2

Combine like terms: 2 + -2 = 0
0 + -3t = -7 + -2
-3t = -7 + -2

Combine like terms: -7 + -2 = -9
-3t = -9

Divide each side by '-3'.
t = 3

Simplifying
t = 3

See similar equations:

| 4x+7=-8x-29 | | 4g-4=40 | | 4+x+7x=76 | | 6-5x=-44 | | 15x(x)-15x=0 | | 1+1-2-x=-4(x+2) | | -9+7x=-65 | | 143-5x=11+6x | | 35+10x=3x | | 15z^3-4z^2=35z | | 11x-97=-9 | | 9-2x=33 | | 12x(x)+3x=0 | | (3x^3/4)(11/15x^2)=0 | | 42-12a=-15a+5 | | 15+x-15=89 | | 9+7x=-65 | | 9.6f+5.8(f+20)=80.8 | | 8z-8=80 | | 71-8x=-17 | | 15x=13x+10 | | -18=30-4x | | -0.9-0.6= | | 5.8f+9.6(20-f)=80.8 | | 5x(x)+50x=0 | | 4=6x+40 | | 4x+5x=3x+4x | | (x-3-2i)(x+3+2i)= | | 15m+-6m= | | 9.6f+5.8(20)=80.8 | | x(x)-9x=0 | | 32=12-4x |

Equations solver categories